Pigou in the 21st Century: a tribute on the occasion of the 100th anniversary of the publication of The Economics of Welfare - Ottmar Edenhofer; Max Franks; Matthias Kalkuhl (International Tax and Public Finance, 2021)
The year 2020 marks the centennial of the publication of Arthur Cecil Pigou's magnum opus The Economics of Welfare. Pigou's pricing principles have had an enduring influence on the academic debate, with a widespread consensus having emerged among economists that Pigouvian taxes or subsidies are theoretically desirable, but politically infeasible. In this article, we revisit Pigou's contribution and argue that this consensus is somewhat spurious, particularly in two ways: (1) Economists are too quick to ignore the theoretical problems and subtleties that Pigouvian pricing still faces; (2) The wholesale skepticism concerning the political viability of Pigouvian pricing is at odds with its recent practical achievements. These two points are made by, first, outlining the theoretical and political challenges that include uncertainty about the social cost of carbon, the unclear relationship between the cost–benefit and cost-effectiveness approaches, distributional concerns, fragmented ministerial responsibilities, an unstable tax base, commitment problems, lack of acceptance and trust between government and citizens as well as incomplete international cooperation. Secondly, we discuss the recent political success of Pigouvian pricing, as evidenced by the German government's 2019 climate policy reform and the EU's Green Deal. We conclude by presenting a research agenda for addressing the remaining barriers that need to be overcome to make Pigouvian pricing a common political practice.
Keywords: Q5; H2; 340; Environmental economics; Climate change economics; Carbon pricing; Pigouvian taxation; Economic policy